Chemical Constituents from Trichosanthis pericarpium - Shi, Guoyu; Xu, Meixia; Duan, Wenjuan; Fang, Lei; Liu, Wei; Wang, Xiao; Zhang, Yongqing (Asian Journal of Chemistry, 2014)
Seventeen compounds were isolated from the Trichosanthis pericarpium using silica gel, MCI, Sephadex, reversed-phase C18 column chromatographies and preparative high-performance liquid chromatography (pre-HPLC). Their chemical structures were elucidated on the basis of detailed spectroscopic analysis, including NMR spectroscopy and ESI-MS analysis. Among which, eight compounds were reported from the genus of Trichosanthes for the first time.